2015
DOI: 10.1103/physrevb.91.155104
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit-induced orbital excitations inSr2RuO4andCa2RuO4: A resonant inelastic x-ray sc

Abstract: High-resolution resonant inelastic x-ray scattering (RIXS) at the oxygen K edge has been used to study the orbital excitations of Ca 2 RuO 4 and Sr 2 RuO 4 . In combination with linear dichroism x-ray absorption spectroscopy, the ruthenium 4d-orbital occupation and excitations were probed through their hybridization with the oxygen p orbitals. These results are described within a minimal model, taking into account crystal field splitting and a spin-orbit coupling λ so = 200 meV. The effects of spin-orbit inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 42 publications
5
40
0
Order By: Relevance
“…The ground-state wave function of the Ru 4+ ion was described in terms of an admixture of xy, yz, and zx orbitals, whose respective contribution depends on the relative strength of the tetragonal crystal field δ and SOC λ [20,[48][49][50][51][52][53]. Within this picture, the tuning of the crystal field caused by the elongation of the RuO 6 octahedra [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ground-state wave function of the Ru 4+ ion was described in terms of an admixture of xy, yz, and zx orbitals, whose respective contribution depends on the relative strength of the tetragonal crystal field δ and SOC λ [20,[48][49][50][51][52][53]. Within this picture, the tuning of the crystal field caused by the elongation of the RuO 6 octahedra [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2 RuO 4 has attracted considerable attention in recent years as the Mott-insulating analogue of the unconventional superconductor Sr 2 RuO 4 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . A welldocumented metal to insulator transition (MIT) occurs at T MIT = 357 K, concomitant with a first-order structural transition from a high-temperature quasitetragonal phase to a low-temperature orthorhombic one (P bca space group) 1,2,4,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between lattice and orbital degrees of freedom was highlighted by recent X-ray near-edge absorption spectroscopy (XANES) studies 5,10,15 , which revealed that the ground-state t 2g orbital population can be effectively tuned by changing the ratio ∆/λ, analogous to the case of the Ir 4+ ion in perovsite iridates 24 . The low-energy electronic structure is thus expected to be extremely sensitive to structural distortions acting on the local Ru 4+ crystalline environment.…”
Section: Introductionmentioning
confidence: 99%
“…RIXS is therefore an attractive complementary technique to neutron scattering. This has, in particular, lead to progress in understanding correlated low-dimensional 3d,4d, and 5d electron systems [11][12][13]. The spin-excitation spectra of insulating one-and two-dimensional cuprates have, for example, been studied by soft x-ray RIXS using the copper L 3 edge [12,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%